PENERAPAN METODE CAPITAL ASSET PRICING MODEL DALAM MENENTUKAN KEPUTUSAN INVESTASI SAHAM - Adhitya Ardhaswara, I Dewa Made; Suarjaya, Anak Agung Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this research is to apply the Capital Asset Pricing Model (CAPM) method to determine the valuation of undervalued and overvalued stocks, as a consideration in making stock investment decisions. The population in this study is the shares of the banking sub-sector on the Indonesia Stock Exchange for the period 2019 – 2020 with a total sample of 40 stocks taken using the saturated sampling method. The analytical technique used is the CAPM analysis technique. Based on the results of the analysis, it was found that 3 stocks were classified as undervalued and 37 stocks were overvalued from 40 stocks of the banking sub-sector which were used as research samples. Investment decisions taken on shares classified as undervalued are considered to buy these shares, while investment decisions taken on shares classified as overvalued are considered to sell these shares. The results of this study are expected to provide an overview of stocks that are worthy of consideration to be chosen in investing for investors and potential investors so that the expected return target can be achieved.